К вопросу о дистантной ориентации плотвы Киевского водохранилища - Абросимова, А.М.; Васина, О.Г.; Гуменюк, С.Б. (Вестник зоологии, 1968)
The experiments on roach orientation depending on season, weather and distance from the place where it was caught were carried out in the Kiev reservoir. A small ball of a definite colour was fastened to a dorsal fin of a fish and by this ball's motion the direction of fish movement was determined by means of a compass. Roach, caught in a definite place was transported in various directions: north, south, east and west. The experiments confirm seasonal fattening and spawning migrations of roach. In sunny weather 30 p. c. of roach comes back to the places of the catch, 49 p. c. migrates south, 10 p. c. — west, Ill p. c.— south west. In cloudy weather only I0 p. c. of roach individuals comes back and 90 p. c. migrates south. With an increase of transportation distance a number of roach individuals coming back, increases.